2007
DOI: 10.1080/13825580600966391
|View full text |Cite
|
Sign up to set email alerts
|

Base Rates of Negative Response Bias and Malingered Neurocognitive Dysfunction among Criminal Defendants Referred for Neuropsychological Evaluation

Abstract: Several studies reveal the prevalence of negative response bias (NRB) in civil forensic settings, but little NRB base rate information is available for criminal forensic neuropsychological settings. We reviewed the published literature on neuropsychological NRB in the civil setting. We then present data from 105 criminal defendants serially referred for neuropsychological assessment to determine the prevalence of NRB. The rate of NRB using one positive indicator was 89.5%. The rate was 70.5% when using two or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
2
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(70 citation statements)
references
References 44 publications
0
61
2
7
Order By: Relevance
“…Although there has been controversy surrounding the FBS and its value (Arbisi and Butcher 2004;Ben-Porath et al 2009;Butcher et al 2003Butcher et al , 2008Greve and Bianchini 2004b;Lees-Haley and Fox 2004;Williams et al 2009), recent studies (Ardolf et al 2007;Bianchini et al 2008;Demakis et al 2008;Sellers et al 2006;Wygant et al 2007) provide evidence of FBS's validity. Unlike the F family and other traditional response-style scales, FBS typically shows a substantial relationship to performance on cognitive SVTs (Larrabee 2003;Sellers et al 2006;Wygant et al 2007; but see Whitney et al 2008).…”
Section: Self-report Inventories and Structured Interviewsmentioning
confidence: 93%
“…Although there has been controversy surrounding the FBS and its value (Arbisi and Butcher 2004;Ben-Porath et al 2009;Butcher et al 2003Butcher et al , 2008Greve and Bianchini 2004b;Lees-Haley and Fox 2004;Williams et al 2009), recent studies (Ardolf et al 2007;Bianchini et al 2008;Demakis et al 2008;Sellers et al 2006;Wygant et al 2007) provide evidence of FBS's validity. Unlike the F family and other traditional response-style scales, FBS typically shows a substantial relationship to performance on cognitive SVTs (Larrabee 2003;Sellers et al 2006;Wygant et al 2007; but see Whitney et al 2008).…”
Section: Self-report Inventories and Structured Interviewsmentioning
confidence: 93%
“…Bianchini et al (2006) reported comparable rates of failure on malingering tests and other validity indicators and diagnosable malingering in TBI and found that rates varied with the magnitude of incentive. Ardolf et al (2007) and Chafetz (2008) reported base rates of 50% or more in a criminal forensic settings and Social Security Disability evaluations, respectively. Rates in patients claiming injuries due to toxic exposures were in a similar range (Greve et al 2006a, b).…”
mentioning
confidence: 97%
“…Chafetz (2008) reported that 45.8-59.7% of adults seeking Social Security disability met criteria for at least probable malingering (i.e., failed two or more validity indicators), with the results varying on samples and SVTs utilized. Ardoff et al (2007) investigated the base rates of negative response bias (i.e., malingering) in a criminal forensic setting. These authors found that among the 105 criminal defendants consecutively referred for neuropsychological assessment, 32.4% met the criteria for probable malingering and 21.9% met criteria for definite malingering, which combined for a definite/probable base rate of malingering of 54.3%.…”
Section: Special Considerations Response Bias Symptom Validity Testingmentioning
confidence: 99%